Cancer-Derived Exosomes: Their Role in Cancer Biology and Biomarker Development - Kok VC (Dove Medical Press, 2020)
Victor C Kok,1,2 Cheng-Chia Yu3,4 1Division of Medical Oncology, Kuang Tien General Hospital Cancer Center, Taichung, Taiwan; 2Department of Bioinformatics and Medical Engineering, Asia University, Taichung, Taiwan; 3Institute of Oral Sciences, Chung Shan Medical University, Taichung, Taiwan; 4School of Dentistry, Chung Shan Medical University, Taichung, TaiwanCorrespondence: Victor C KokDivision of Medical Oncology, Kuang Tien General Hospital Cancer Center, 117 Shatien Road, Shalu, Taichung 43303, TaiwanTel +886 4 2662 5111 Ext 2263Fax +886 4 2665 5050Email vkok@alumni.harvard.eduAbstract: Exosomes are a subset of tiny extracellular vesicles manufactured by all cells and are present in all body fluids. They are produced actively in tumor cells, which are released and utilized to facilitate tumor growth. Their characteristics enable them to assist major cancer hallmarks, leveraged by cancer cells in fostering cancer growth and spread while implementing ways to escape elimination from the host environment. This review updates on the latest progress on the roles of cancer-derived exosomes, of 30– 100 nm in size, in deregulating paracrine trafficking in the tumor microenvironment and circulation. Thus, exosomes are being exploited in diagnostic biomarker development, with its potential in clinical applications as therapeutic targets utilized in exosome‐based nanoparticle drug delivery strategies for cancer therapy. Ongoing studies were retrieved from PubMed® and Scopus database and ClinicalTrials.gov registry for review, highlighting how cancer cells from entirely different cell lines rely on genetic information carried by their exosomes for homotypic and heterotypic intercellular communications in the microenvironment to favor proliferation and invasion, while establishing a pre-metastatic niche in welcoming cancer cells’ arrival. We will elaborate on the trafficking of tumor-derived exosomes in fostering cancer proliferation, invasion, and metastasis in hematopoietic (leukemia and myeloma), epithelial (breast cancer), and mesenchymal (soft tissue sarcoma and osteosarcoma) cancers. Cancer-derived exosomal trafficking is observed in several types of liquid or solid tumors, confirming their role as cancer hallmark enabler. Their enriched genetic signals arising from their characteristic DNA, RNA, microRNA, and lncRNA, along with specific gene expression profiles, protein, or lipid composition carried by the exosomal cargo shed into blood, saliva, urine, ascites, and cervicovaginal lavage, are being studied as a diagnostic, prognostic, or predictive cancer biomarker. We reveal the latest research efforts in exploiting the use of nanoparticles to improve the overall cancer diagnostic capability in the clinic.Keywords: tumor-released exosomes, carcinoma-associated fibroblasts, exosome cargo, exosome-induced chemoresistance, hallmarks of cancer, tumor-stromal communications